2015
DOI: 10.1002/smll.201501766
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal Boron Nitride–Graphene Heterostructures: Synthesis and Interfacial Properties

Abstract: Research on in-plane and vertically-stacked heterostructures of graphene and hexagonal boron nitride (h-BN) have attracted intense attentions for energy band engineering and device performance optimization of graphene. In this review article, recent advances in the controlled syntheses, interfacial structures, and electronic properties, as well as novel device constructions of h-BN and graphene heterostructures are highlighted. Firstly, diverse synthesis approaches for in-plane h-BN and graphene (h-BN-G) heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(105 citation statements)
references
References 130 publications
(273 reference statements)
1
104
0
Order By: Relevance
“…Significant research interest has been given to develop atomically thin 2D heterostructure of graphene and hexagonal boron nitride (hBN) [100]. hBN can be considered as a structural analogue of graphene, which is composed of alternating boron and nitrogen atoms in a honeycomb lattice rather than the carbon atoms.…”
Section: Graphene-hexagonal Boron Nitride Heterostructurementioning
confidence: 99%
See 1 more Smart Citation
“…Significant research interest has been given to develop atomically thin 2D heterostructure of graphene and hexagonal boron nitride (hBN) [100]. hBN can be considered as a structural analogue of graphene, which is composed of alternating boron and nitrogen atoms in a honeycomb lattice rather than the carbon atoms.…”
Section: Graphene-hexagonal Boron Nitride Heterostructurementioning
confidence: 99%
“…hBN can be considered as a structural analogue of graphene, which is composed of alternating boron and nitrogen atoms in a honeycomb lattice rather than the carbon atoms. Graphene with a zero bandgap is a semimetallic as discussed in Section 1, while hBN with a bandgap of ~6 eV is insulating [100][101][102][103][104][105][106][107]. Significant carrier mobility of graphene has been achieved on atomically flat hBN as a dielectric layer for the FET device.…”
Section: Graphene-hexagonal Boron Nitride Heterostructurementioning
confidence: 99%
“…They also demonstrated that as-synthesized graphene films could be transferred to other substrates (Figure 1b and c). To meet some special requirements, non-metal materials, such as Si [14,15], SiO 2 [26][27][28], BN [29,30] and Si 3 N 4 [31,32], were also used as substrates. However, the non-metal substrates showed the drawback limitations including slow growth rate and discontinuous size.…”
Section: Chemical Vapour Depositionmentioning
confidence: 99%
“…8 A comprehensive overview of the current status of the different synthesis processes for BN has demonstrated formation of different properties for BN powders highlighting the advantages of every synthetic methods. [9][10][11][12][13][14][15][16][17][18][19][20] Solar heating is a promising alternative energy source for nanotechnology. A xenon high-flux optical simulator (also artificial sun) that provides illumination approximating natural sunlight in controllable indoor tests under laboratory conditions is a good model of this source.…”
Section: Introductionmentioning
confidence: 99%